2007
DOI: 10.1111/j.1365-2036.2007.03251.x
|View full text |Cite
|
Sign up to set email alerts
|

Barrett’s oesophagus: long‐term follow‐up after complete ablation with argon plasma coagulation and the factors that determine its recurrence

Abstract: SUMMARY BackgroundArgon plasma coagulation seems to be a promising technique for ablation of Barrett's oesophagus, yet few long-term efficacy data are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 25 publications
4
32
0
1
Order By: Relevance
“…Th ere is some evidence from uncontrolled observational studies to suggest that incomplete control of refl ux may be associated with increased recurrence rates following successful endotherapy ( 189,190 ). However, there is currently a lack of conclusive evidence to suggest that high-dose PPI therapy or tight control of refl ux (as determined by ambulatory pH monitoring) leads to lower recurrence rates following ablation.…”
Section: Management Of Be After Endoscopic Therapymentioning
confidence: 99%
“…Th ere is some evidence from uncontrolled observational studies to suggest that incomplete control of refl ux may be associated with increased recurrence rates following successful endotherapy ( 189,190 ). However, there is currently a lack of conclusive evidence to suggest that high-dose PPI therapy or tight control of refl ux (as determined by ambulatory pH monitoring) leads to lower recurrence rates following ablation.…”
Section: Management Of Be After Endoscopic Therapymentioning
confidence: 99%
“…Medical therapy with maximal acid suppression has generally shown poor rates of Barrett's metaplasia regression, and an optimal protocol for surveillance is yet to be fully validated [17][18][19]. Issues with respect to these techniques have centered around incomplete ablation, especially this issue of ''buried glands'' (i.e., Barrett's metaplasia persistent under of layer of normal squamous epithelium) [8][9][10][20][21][22]. The problem is that this buried metaplasia is capable of developing into carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Toward this end, a strict protocol of twice per day proton pump inhibitors reduces the risk of Barrett's recurrence. Others also have noted that aggressively reducing acid reflux lowers the risk of Barrett's recurrence for both argon plasma coagulation and endoscopic radiofrequency ablation [21,26]. The alternative is an antireflux operation, such as a laparoscopic Nissen fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports attribute this to the failure of proton pump inhibitor therapy to control esophageal acidity [29,30,31]. Indeed, Kahaleh et al [32] observed that following Barrett's ablation by argon plasma coagulation, pH monitoring was abnormal in 69% of patients (i.e.…”
Section: Neosquamous Epitheliummentioning
confidence: 99%
“…This occurs in two ways: (1) loss of barrier function by NSE allows greater access of luminal contents to buried Barrett's glands [11,37,38], and (2) reflux-induced injury to NSE produces inflammation whose byproducts, prostaglandins, oxy-free radicals, and cytokines, expose buried Barrett's glands to known promoters of cell turnover and malignancy [39,40,41,42,43]. In keeping with this concern is the fact that esophageal adenocarcinoma is known to occur in buried Barrett's glands [44,45,46] and buried Barrett's glands have been found in up to 44% of patients following Barrett's ablation by argon plasma coagulation [26,27,29,47]. Notably, the prevalence of buried BE following radiofrequency ablation is reported to be far lower, i.e.…”
Section: Neosquamous Epitheliummentioning
confidence: 99%